2021
DOI: 10.1080/08038740.2021.1888791
|View full text |Cite
|
Sign up to set email alerts
|

Bodies get in the way: breastfeeding and gender equality in Swedish handbooks for new parents

Abstract: This article offers an analysis of three popular Swedish handbooks for new parents, written by authors in the "media class." In these texts breastfeeding as a gendered, embodied practice collides with the Swedish ideal of genderequal parenting. The analysis explores the various ways that gendered bodies, gendered (parental) rights, and gender equality figure in the handbooks, drawing upon feminist studies of bodies and embodiment, and of breastfeeding in particular. It contextualizes the primary texts in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The impact on breastfeeding of societal expectations that mothers and fathers should share infant care equally, such as in Scandinavia, should also be considered. In Sweden, parenting handbooks position breastfeeding as a ‘gender equality problem,’ and describe breastfeeding as alienating fathers because it distances them from newborns and makes them unimportant ( 125 ). Research from Norway found that some fathers felt jealous of the mother–child relationship and sad and excluded when women breastfed ( 126 ).…”
Section: Introductionmentioning
confidence: 99%
“…The impact on breastfeeding of societal expectations that mothers and fathers should share infant care equally, such as in Scandinavia, should also be considered. In Sweden, parenting handbooks position breastfeeding as a ‘gender equality problem,’ and describe breastfeeding as alienating fathers because it distances them from newborns and makes them unimportant ( 125 ). Research from Norway found that some fathers felt jealous of the mother–child relationship and sad and excluded when women breastfed ( 126 ).…”
Section: Introductionmentioning
confidence: 99%